2019
DOI: 10.2147/cia.s230008
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effectiveness of a Mini-Trampoline Training Program on Balance and Functional Mobility, Gait Performance, Strength, Fear of Falling and Bone Mineral Density in Older Women with Osteopenia</p>

Abstract: Purpose: To evaluate the effectiveness of a combined balance-, strength-, and jumpingexercise intervention on a mini-trampoline performed by older women with osteopenia on static balance and functional mobility, gait speed, strength of the upper and lower limbs, fear of falling, as well as to investigate its influence on bone mineral density (BMD). Patient and methods: Using a randomized controlled study design, participants (range: 56-83 years) were assigned either to the intervention group (IG; n=20, mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 68 publications
0
14
2
1
Order By: Relevance
“…Studies. Among the 10 identified RCTs, three studies were in English [16][17][18] and seven in Chinese [19][20][21][22][23][24][25]. Publication year ranged from 2009 [17] to 2019 [21], and all studies were two-arm trials.…”
Section: Characteristics Of the Identifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies. Among the 10 identified RCTs, three studies were in English [16][17][18] and seven in Chinese [19][20][21][22][23][24][25]. Publication year ranged from 2009 [17] to 2019 [21], and all studies were two-arm trials.…”
Section: Characteristics Of the Identifiedmentioning
confidence: 99%
“…Eight studies specifically described adequate random sequence generation methods, including envelope method and random number table [16][17][18][19][20][22][23][24]. Given the particularity of nonpharmacological interventions, it was extremely difficult to blind both the patients and the personnel to treatment, and only three studies described sufficient allocation concealment and the specific implementation methods for blind evaluation of outcome measures [16][17][18]. Six studies reported loss of follow-up during treatment, explaining the number of lost cases and specific reasons [16-19, 22, 23].…”
Section: Risk Of Bias Of the Individual Studiesmentioning
confidence: 99%
“…While in the case of post-CA exercise, trampoline-based plyometric exercise (with the supporting bars or on the sledge) [ 53 , 61 ] can be considered as the safest option for the elderly, suitable for the first stage of periodisation in longitude complex training. Then, this could be progressed by the introduction of suspension exercises (e.g., jump squats using suspension straps).…”
Section: Post-activation Performance Enhancement and Complex Trainingmentioning
confidence: 99%
“…Определена МПКТ при помощи двухэнергетической рентгеновской абсорбциометрии на аппарате HOLOGIС по шейке бедра и поясничному отделу позвоночника в начале исследования и через 12 месяцев [9].…”
Section: материалы и методыunclassified